Matrix algebra and vector algebra - Ng, Set Foong; Foo, Fong Yeng; Mahat, Aishah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2026)
Matrix Algebra and Vector Algebra is an academic book that covers a series of topics in mathematics such as operations on matrices, determinants, inverse matrices, vector in two- and three-dimensional space. With the exposure of these basic concepts in matrix and vector algebra, students would be able to understand and apply the knowledge in solving system of linear equations using matrix and solving simple geometric applications. The concept of each topic is explained in the beginning of each chapter. Examples are given to illustrate the concept. Detailed steps are shown on how to solve the problems. This module is